2017
DOI: 10.1111/risa.12956
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Leukemia Risk in Human Populations Exposed to Benzene from Tobacco Smoke Using Epidemiological Data

Abstract: Several epidemiological studies have demonstrated an association between occupational benzene exposure and increased leukemia risk, in particular acute myeloid leukemia (AML). However, there is still uncertainty as to the risk to the general population from exposure to lower environmental levels of benzene. To estimate the excess risk of leukemia from low‐dose benzene exposure, various methods for incorporating epidemiological data in quantitative risk assessment were utilized. Tobacco smoke was identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Benzene is widely used as a solvent in industrial processes such as production of chemicals and plastics as well as oil processing. Tobacco smoke was also identified as one of the main potential sources of benzene exposure (30,31). Use of tobacco is associated with a small increase in the risk of developing acute myeloid leukemia in adults (32).…”
Section: Discussionmentioning
confidence: 99%
“…Benzene is widely used as a solvent in industrial processes such as production of chemicals and plastics as well as oil processing. Tobacco smoke was also identified as one of the main potential sources of benzene exposure (30,31). Use of tobacco is associated with a small increase in the risk of developing acute myeloid leukemia in adults (32).…”
Section: Discussionmentioning
confidence: 99%
“…Workers exposed to benzene have shown higher leukaemia incidence. 5 , 6 Higher rates of leukaemia have also been observed among Japanese atomic bomb survivors and Ukrainian Chernobyl clean-up workers. 7 , 8 Studies of agricultural workers and pesticide applicators have also shown elevated risks among certain subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the relationship of the smoking habit and benzene health effects, several authors have found that it is an important source of environmental benzene contamination, and it is directly related to some adverse health outcomes. 60 , 61 In this review, most studies predicted that smoking was a confounding factor and therefore adjusted their analysis to have more reliable results. For instance, some of the reviewed papers found that the smoking habit correlates with worse health outcomes and suggested that future research should take into account this factor while studying occupational exposure.…”
Section: Discussionmentioning
confidence: 99%